New Findings by High-Order DNS for Late Flow Transition in a Boundary Layer - Chaoqun Liu; Lin Chen; Ping Lu (Modelling and Simulation in Engineering)
This paper serves as a summary of new discoveries by DNS for late stages of flow transition in a boundary layer. The widely spread concept “vortex breakdown” is found theoretically impossible and never happened in practice. The ring-like vortex is found the only form existing inside the flow field. The ring-like vortex formation is the result of the interaction between two pairs of counter-rotating primary and secondary streamwise vortices. Following the first Helmholtz vortex conservation law, the primary vortex tube rolls up and is stretched due to the velocity gradient. In order to maintain vorticity conservation, a bridge must be formed to link two Λ-vortex legs. The bridge finally develops as a new ring. This process keeps going on to form a multiple ring structure. The U-shaped vortices are not new but existing coherent vortex structure. Actually, the U-shaped vortex, which is a third level vortex, serves as a second neck to supply vorticity to the multiple rings. The small vortices can be found on the bottom of the boundary layer near the wall surface. It is believed that the small vortices, and thus turbulence, are generated by the interaction of positive spikes and other higher level vortices with the solid wall. The mechanism of formation of secondary vortex, second sweep, positive spike, high shear distribution, downdraft and updraft motion, and multiple ring-circle overlapping is also investigated.